ANALISIS TRANSFORMASI STRUKTURAL DAN POTENSI SUMBER DAYA MANUSIA DI KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - Musniasih Yuniati; Yorman Kasman (KOLONI, 2022)
Structural transformation is a way for developing countries to increase their economic growth by transforming their economic structure from the traditional agricultural sector to the manufacturing sector and the service sector.  This condition must be balanced by adequate human resource potential.  Central Lombok district.  The research method used descriptive qualitative method.  The analysis was carried out qualitatively based on quantitative data.  The results showed that there had been a structural transformation in Central Lombok district which was marked by a decrease in the contribution of the agricultural sector and an increase in the contribution of the manufacturing and service sectors to GRDP Human resource potential Central Lombok Regency consists of a  population that increases from year to year, the number of working people, the number of unemployed people and the number of people who take care of the household and the number of young people. Keywords: Structural transformation, Human resource potential